Serum of patients with acute myocardial infarction prevents inflammation in iPSC-cardiomyocytes - Sattler, Katherine; El-Battrawy, Ibrahim; Zhao, Zhihan; Schrottenberg, Christoph; Yücel, Gökhan; Lan, Huan; Li, Xin; Lang, Siegfried; Zimmermann, Wolfram-Hubertus; Cyganek, Lukas; Utikal, Jochen; Wieland, Thomas; et al. (Scientific reports, 2019)
Acute myocardial infarction (MI) evokes a systemic inflammatory response and locally the degradation of the necrotic tissue, followed by scar formation. The mechanisms for containment of the infarct zone are not studied well. The study aimed to examine the response of healthy cardiomyocytes to serum of patients with myocardial infarction. Human iPSC-cardiomyocytes (iPSC-CM) generated from two healthy donors were incubated with serum of patients with MI with and without ventricular fibrillation (VF) or of healthy controls. Different cell adhesion molecules were studied by flow cytometry and immunostaining. Cellular electrophysiology was studied by patch clamp. The cell adhesion molecules CD54/ICAM-1, CD58/LFA-3 and CD321/JAM-A were expressed on iPSC-CM within the plasma membrane. Incubation with serum of MI patients reduced the levels of expression of CD54/ICAM-1 and CD321/JAM-A by 15-20%. VF serum was less effective than serum of MI patients without VF. MI serum or VF serum did not affect resting potential, action potential duration or maximum depolarization velocity. Myocardial infarction serum exerts anti-inflammatory effects on healthy cardiomyocytes without affecting their electrical activity, thus helping to contain the infarct zone and to protect healthy tissue. Ventricular fibrillation during MI drives healthy cardiomyocytes towards a pro-inflammatory phenotype.